1984
DOI: 10.2307/2948030
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Household Distribution of Contraceptives in Zaire

Abstract: All use subject to http://about.jstor.org/terms rates were highest among users of the pill and lowest among users of foam. Among women who were no longer using their contraceptive method, the main reason given was that the woman had become pregnant (22 percent of urban women and 33 percent of rural residents).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the Democratic Republic of Congo, the task-shifting of family planning (FP) services is not a new idea [1] , but the commitment of the country to the FP2020 initiative since 2012 has boosted the interest for community-based provision of contraceptives as a way to decrease unmet need 1 for FP. The use of Community-Based Distributors (CBDs) for contraceptive provision is a key element of the National Strategic Plan for Family Planning [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Democratic Republic of Congo, the task-shifting of family planning (FP) services is not a new idea [1] , but the commitment of the country to the FP2020 initiative since 2012 has boosted the interest for community-based provision of contraceptives as a way to decrease unmet need 1 for FP. The use of Community-Based Distributors (CBDs) for contraceptive provision is a key element of the National Strategic Plan for Family Planning [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Quasiexperimental studies have shown that CBD programmes have a significant positive impact on contraceptive prevalence rates, [3][4] while others, using the same study design have arrived at inconclusive findings. [5][6] Moreover, lessons from countries with large national CBD programmes confuse the matter further. For instance, in Kenya the plateauing of the national contraceptive prevalence rate over the past ten years 7 has been blamed on the curtailment of the country's CBD programme due to funding constraints.…”
Section: Introductionmentioning
confidence: 99%
“…CBD programs in sub-Saharan Africa in the 1960s and the pilot projects of the 1970s and 1980s demonstrated the feasibility of this approach to family planning service delivery, particularly in rural areas without clinical resources (Ampofo et al, 1976;Cuca and Pierce, 1977;University of Ghana and UCLA, 1979;Bertrand et al, 1984;and Ross, 1990). The Fertility Research Unit, sponsor of the subject of this report, developed a pilot CBD project in rural Oyo State, Nigeria, which has been extended by the State Ministry of Health (Ladipo et al, 1985;Delano, 1987).…”
mentioning
confidence: 99%